Analisis Biaya Operasional Kendaraan (BOK) Akibat Dari Pembangunan Jalan Baru: Studi Kasus Pembangunan Ruas Jalan Latoma-Routa Kabupaten Konawe - Muammar Makmur; Adris Ade Putra; Riyan Abdillah Takdir; Muzammil Makmur (Jurusan Teknik Sipil, Universitas Halu Oleo, 2024)
The development of road infrastructure plays a crucial role in supporting economic growth and improving community welfare. One of the important indicators that need to be analyzed in the context of road infrastructure development is Vehicle Operating Cost (VOC). With the construction of new road sections, there is significant potential for changes in VOC. Several factors that can affect VOC due to new road construction include improved road quality, reduced congestion, and changes in travel distance. This study aims to analyze the impact of new road construction on VOC. The research will explore to what extent the new road construction can provide cost efficiency for vehicle users. The method used to analyze Vehicle Operating Cost (VOC) is the travel speed method developed by PT Jasa Marga in collaboration with LAPI ITB. Based on the analysis, the VOC savings is the difference between the VOC of the existing Latoma-Routa road section and the VOC of the new Latoma-Routa road section. This cost saving is the benefit value of the construction of the new Latoma-Routa road section due to the travel distance savings of 145.27 km from Latoma to Routa or vice versa. Based on the analysis results, the VOC savings for motorcycles is Rp. 97,177 per vehicle, for cars is Rp. 912,987 per vehicle, and for trucks is Rp. 1,198,907 per vehicle.